2020
DOI: 10.3390/genes11101221
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Architecture Underpinning Yield Components and Seed Mineral–Nutrients in Sesame

Abstract: Genetic dissection of yield components and seed mineral-nutrient is crucial for understanding plant physiological and biochemical processes and alleviate nutrient malnutrition. Sesame (Sesamum indicum L.) is an orphan crop that harbors rich allelic repertoire for seed mineral–nutrients. Here, we harness this wide diversity to study the genetic architecture of yield components and seed mineral–nutrients using a core-collection of worldwide genotypes and segregating mapping population. We also tested the associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 56 publications
(78 reference statements)
0
25
2
Order By: Relevance
“…The advantage of using a diversity panel to detect new alleles is exemplified by comparing our results with a bi-parental population that was grown under the same environmental conditions. While Teboul et al [ 3 ] detected six QTLs using the F 2 population (S-91 × S-297), only the genomic region on LG11 was overlap with the current study.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…The advantage of using a diversity panel to detect new alleles is exemplified by comparing our results with a bi-parental population that was grown under the same environmental conditions. While Teboul et al [ 3 ] detected six QTLs using the F 2 population (S-91 × S-297), only the genomic region on LG11 was overlap with the current study.…”
Section: Discussioncontrasting
confidence: 59%
“…Sesame is an annual diploid (2n = 2x = 26) species, which belongs to the Sesamum genus from the Pedaliaceae family. Its seeds are comprised of oil (45–60%), proteins (18-25%), carbohydrates (3-25%), and are rich in essential vitamins and mineral-nutrients [ 2 , 3 ]. The seeds are being used for an array of products in the food (e.g., high-quality oil, tahini paste, and cooking and backing) and pharmaceutical industries [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The advantage of using a diversity panel to detect new alleles is exemplified by comparing our results with a bi-parental population that was grown under the same environmental conditions. While Teboul et al (2020) detected six QTLs using the F2 population (S-91 × S-297), only the genomic region on LG11 was overlap with the current study.…”
Section: Genetic Architecture Of Agronomical Traits Reveals Hotspot Of Overlapping Genomic Regionscontrasting
confidence: 49%
“…Seed size (TSW) is known to have moderatehigh heritability in sesame (Uzun et al, 2013;Kalaiyarasi et al, 2019), as was found in the current study (0.88) and other crops, such as wheat (Sukumaran et al, 2018) and pea (Pisum sativum L.; Huang et al, 2017), was associated with only one region in 2020, with no overlap with SNPP and SYPP. Likewise, a small number of associated loci for TSW were found in bi-parental sesame populations (Du et al, 2019;Teboul et al, 2020), which may suggest that this trait is under less complex genetic control or under the regulation of many small-effect genomic regions. The absence of significant genomic signs for TSW (as well as other traits in the current study) indicates that other approaches, such as genomic prediction (Crossa et al, 2017), may contribute to understanding its genetic basis.…”
Section: Genetic Architecture Of Agronomical Traits Reveals Hotspot Of Overlapping Genomic Regionsmentioning
confidence: 99%
See 1 more Smart Citation